PENGARUH KOMUNIKASI INTERPERSONAL DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI SMA SE-KOTA PUTUSSIBAU - Husni Syahrudin (STKIP Persada Khatulistiwa Sintang, 2022)
Learning is a need of every human being. Learning achievement achieved by students is influenced by many factors, both internal and external. The purpose of this study was to determine the effect of interpersonal communication skills and student motivation on learning achievement in economic subjects during the COVID-19 pandemic at Putussibau City High School. The research method used is the explanatory survey method. The research population of all students who are in class XI of all SMA there are 236 students and with a total sample of 127 students. Then the data analysis was done descriptively and inferentially with the help of SPSS. Based on the description test data on interpersonal communication variables, including the medium category and leading to high. The motivation variable shows the category is quite good when online learning is applied in schools. While learning achievement shows in the medium category. Based on the results of data analysis that has been carried out, it shows that there is a significant influence, either partially or simultaneously, the influence of interpersonal communication skills and student motivation on Economics subjects in class XI in all high schools in Putussibau city.